Dysregulation of Rab5‐mediated endocytic pathways in Alzheimer's disease. (5th February 2018) - Xu, Wei; Fang, Fang; Ding, Jianqing; Wu, Chengbiao
Abstract : Increasing evidence has pointed to that dysregulation of the endo‐lysosomal system is an early cellular phenotype of pathogenesis for Alzheimer's disease (AD). Rab5, a small GTPase, plays a critical role in mediating these processes. Abnormal overactivation of Rab5 has been observed in post‐mortem brain samples of Alzheimer's patients as well as brain samples of mouse models of AD. Recent genome‐wide association studies of AD have identified RIN3 (Ras and Rab interactor 3) as a novel risk factor for the disease. RIN3 that functions as a guanine nucleotide exchange factor for Rab5 may serve as an important activator for Rab5 in AD pathogenesis. In this review, we present recent research highlights on the possible roles of dysregulation of Rab5‐mediated endocytic pathways in contributing to early pathogenesis of AD. Abstract : Dysregulation of the endo‐lysosomal system has emerged as one of the early cellular pathologies for Alzheimer's disease (AD). Rab5 is a small GTPase that plays a critical role in mediating internalization and endocytic trafficking. Recent studies have demonstrated Rab5 is hyperactivated and Rab5 + early endosomes are found to be abnormally enlarged in post‐mortem brain of AD patients and in mouse models of AD. In this review, we summarize recent research findings linking Rab5 dysfunction to AD pathogenesis.